Single component UV curable conformal coating with moisture post cure
By using components such as isocyanate functional acrylic polyurethane and acrylate units in the insulating protective coating, combined with the dual mechanism of UV light curing and moisture curing, the problem of shadow curing on complex-shaped circuit boards is solved, achieving better hardness, solvent resistance and thermal shock resistance.
Patent Information
- Application Number
- JP2024557244
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-04
- Filing Date
- 2023-04-04
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-04-04
AI Technical Summary
In the prior art, UV light curing insulating protective coatings have a "shadow curing" problem on circuit boards of complex shapes, resulting in some areas not being sufficiently cured, affecting hardness and solvent resistance.
Insulating protective coatings are employed that include an isocyanate functional acrylic polyurethane, acrylate unit of 30-65% by weight, a photoactivator of 3.5-5.5% by weight, and antifoaming agent of 0.1-1% by weight, dehydrating agent of 0.5-1.5% by weight, wetting agent of 0.2-1.5% by weight, and a coupling agent of 0.5-2.5% by weight. The coating has both UV light curing and moisture curing dual curing mechanisms, ensuring that all areas can be fully cured.
The coating exhibits better performance retention in high temperature aging tests, provides improved thermal shock resistance and solves shadow curing problems with more uniform curing and higher hardness and solvent resistance.
Smart Images

Figure 2025512834000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conformal coating composition, a method of conformally coating a substrate with the composition, and substrates coated with the composition. [Background technology]
[0002] Conformal coating materials are thin polymeric films that conform to the contours of a printed circuit board to protect the board's components. They are typically applied at thicknesses of 25 to 250 μm and are applied to electronic circuits to protect them from moisture, dust, chemicals, and extreme temperatures.
[0003] The coating can be applied in many ways, including brushing, spraying, dispensing, and dip coating. Additionally, many materials can be used as conformal coatings, such as acrylics, silicones, polyurethanes, and parylenes. Polyurethane coatings are a popular choice for conformal coatings due to their high chemical resistance, flexibility, and hardness.
[0004] Actinically curable coatings (e.g., "UV coatings") are utilized as conformal coatings because such coatings can be cured relatively quickly by exposure to radiation sources, typically UV, including conventional UV (arc and microwave types) and UV-LED sources. Fast curing allows manufacturers to increase throughput. However, because circuit boards and other electronic components have highly contoured surfaces, such UV coatings, when used as conformal coatings, suffer from the phenomenon that areas of the coating that cannot be easily exposed to UV light due to their contours (i.e., "shadow" areas) remain uncured.
[0005] U.S. Patent No. 4,424,252 describes the problem of "shadow curing" and uses dual sulfide resins to solve such problems. Such resins cure by two mechanisms: a) exposure to UV light and b) atmospheric moisture curing. The atmospheric moisture reacts with free isocyanate groups in the dual sulfide resin to form amine groups. The amine groups react with other isocyanate groups to form polyureas. The atmospheric moisture curing allows areas of the coating in the "shadow" to fully cure.
[0006] However, dual sulfide polyurethane resins have suffered from problems due to their relatively high viscosity, which is particularly relevant for conformal coatings due to the contoured shape of the substrate. From a flow standpoint, low viscosity resins are more preferable, i.e., they flow more easily around the contours of a circuit board and can coat such boards more uniformly.
[0007] Previous attempts to reduce the viscosity of dual sulfur polyurethane resins have involved adding significant amounts of reactive diluents to the dual sulfur polyurethane resins. While the addition of the reactive diluents helped to reduce the viscosity of the resin, it also reduced the weight percent of free isocyanate groups in the resin. This in turn has the effect of reducing the effectiveness of the moisture cure mechanism, especially in shadow areas, resulting in a coating that has insufficient hardness and / or solvent resistance in such areas.
[0008] US Patent No. 9,932,492 describes a one-component dual sulfurized conformal coating composition containing an isocyanate-functional urethane acrylate and a polyisocyanate containing allophanate and / or uretdione groups. The composition is said to provide a coating with high hardness and solvent resistance. Conformal coating compositions are also disclosed in US Patent Application Publication No. 2014 / 199491 (A1), Chinese Patent Publication No. 109321125 (A), Chinese Patent Publication No. 111548726 (A), and Chinese Patent Publication No. 111471337 (A).
[0009] To date, conventional conformal coating compositions exhibit undesirable changes in their properties after aging at high temperatures, which can result in stress cracking that causes the conformal coating to provide inadequate protection to circuit boards or electronic components when used in high temperature environments. Summary of the Invention
[0010] The present invention seeks to address at least some of the problems associated with the prior art, or at least provide a commercially acceptable alternative thereto. Additionally, the present invention discloses the construction / fabrication of new assemblies, devices, and components using the disclosed materials and processes.
[0011] In a first aspect, the present invention provides a UV and moisture curable conformal coating composition comprising: 25 to 65 weight percent of an isocyanate-functional acrylated polyurethane; 30 to 65% by weight of an acrylic monomer; 3.5 to 5.5 wt. % of a photoinitiator; 0.1 to 1% by weight of a defoamer, 0.5 to 1.5% by weight of a dehydrating agent, 0.2 to 1.5% by weight of a wetting agent, and 0.5-2.5 wt.% of a coupling agent.
[0012] Each aspect or embodiment defined in this specification may be combined with any other aspect or embodiment unless expressly indicated otherwise. In particular, any feature indicated as being preferred or advantageous may be combined with any other feature indicated as being preferred or advantageous.
[0013] The inventors have surprisingly found that the compositions of the present invention exhibit improved retention of properties during heat aging testing at 130° C., as compared to conventional conformal coating compositions. Advantageously, this can result in improved thermal shock resistance compared to existing technology. Without being bound by theory, it is believed that this is due to the combination of the recited amounts of acrylated polyurethane, acrylic monomer, and photoinitiator.
[0014] The composition has a favorably low glass transition temperature (T g ) and preferably high elasticity (low modulus), which may be particularly suitable for protecting circuit boards during use. Without wishing to be bound by theory, this is believed to be due to the combination of the recited amounts of acrylated polyurethane and acrylic monomer.
[0015] Advantageously, compared to conventional conformal coating compositions, the compositions of the present invention can undergo a slower and more controlled polymerization process during UV curing. This reduces the level of internal stress, which can improve the ability to resist stress cracking during thermal shock excursion. However, curing can still be fast enough to be used in conventional conformal coating production methods and assembly lines. Without being bound by theory, it is believed that this is due to the combination of the listed amounts of acrylated polyurethane, acrylic monomer, and photoinitiator.
[0016] As used herein, the term "conformal coating composition" can include compositions for forming conformal coatings on, for example, circuit boards.
[0017] The composition comprises an isocyanate-functional acrylated polyurethane (acrylated polyurethane containing isocyanate functionality). As used herein, the term "polyurethane" may include a class of polymers composed of organic units linked by carbamate (urethane) bonds. As used herein, the term "acrylated polyurethane" may include polyurethanes that contain acrylate functionality in addition to free isocyanate functionality. The acrylate functionality may also include methacrylate functionality. The isocyanate-functional acrylated polyurethane is preferably in the form of an oligomer.
[0018] The composition is both UV curable and moisture curable. The composition contains secondary moisture curing functionality to ensure cure in areas shaded by exposure to actinic radiation. When exposed to actinic radiation (typically UV), the photoinitiator can cause a reaction between the acrylate functionality on the acrylated polyurethane and the acrylic monomer. When exposed to moisture (typically moisture contained in air), the isocyanate functionality can form amine groups, which can then react with other isocyanate groups to form polyureas.
[0019] The composition includes 0.1 to 1.0 wt.% of an antifoaming agent. The presence of the antifoaming agent in the recited amounts can inhibit the generation of air bubbles during storage and / or use.
[0020] The composition includes 0.5-1.5% by weight of a dehydrating agent. The presence of the dehydrating agent in the recited amounts may inhibit undesirable moisture cure of the composition during storage.
[0021] The composition includes 0.2-1.5 wt. % of a wetting agent. The presence of the wetting agent in the recited amounts may improve the ability of the composition to "wet" the substrate to which the composition is applied, such as a circuit board. In particular, the composition may "wet" all of the components of the circuit board.
[0022] The composition includes 0.5-2.5 wt.% of a coupling agent. The presence of the coupling agent in the recited amounts may improve adhesion of the final conformal coating to the substrate to which it is applied.
[0023] The composition is preferably a "single component" composition.
[0024] The composition preferably comprises 30-50 wt% isocyanate functional acrylated polyurethane, more preferably 35-45 wt% isocyanate functional acrylated polyurethane. The presence of such an amount of isocyanate functional acrylated polyurethane may further improve the properties of retention of properties during heat aging, preferably low glass transition temperature, preferably high elasticity, and slower and more controlled polymerization process during UV curing.
[0025] The isocyanate-functional acrylated polyurethane is preferably a thermoplastic. The isocyanate-functional acrylated polyurethane is preferably an elastomer. The isocyanate-functional acrylated polyurethane is preferably an isocyanate-functional acrylated thermoplastic polyurethane elastomer. This may result in a particularly preferred low glass transition temperature and / or high elasticity of the conformal coating formed by the composition.
[0026] The isocyanate-functional acrylated polyurethane preferably has a ratio of acrylate functional groups to isocyanate functional groups of 2:1 to 1:2, which can provide a particularly favorable amount of crosslinking during curing, i.e., not too low, causing insufficient curing, and not too high, resulting in a hard, inflexible coating.
[0027] The isocyanate-functional acrylated polyurethane is preferably a reaction product of reactants including the following species: at least one polyol, preferably an amorphous hydrophobic polyol, at least one diisocyanate, preferably a branched diisocyanate, and at least one hydroxyalkyl acrylate;
[0028] Typically, a diisocyanate is reacted with a polyol to give an isocyanate-terminated "prepolymer," and then in a second step the prepolymer is further reacted with a hydroxyalkyl acrylate to form an isocyanate-functional acrylated polyurethane.
[0029] The polyol (preferably an amorphous hydrophobic polyol) preferably comprises: one or more of hydroxy-terminated polybutadiene, hydroxy-terminated hydrogenated polybutadiene, hydroxy-terminated polyisoprene, hydroxy-terminated polyolefin, hydroxy-terminated polyfarnesene, hydroxy-terminated hydrogenated polyfarnesene, castor oil, hydrogenated castor oil, and dimer acid-based polyester polyol (preferably C36), more preferably one or more of hydroxy-terminated hydrogenated polybutadiene, hydroxy-terminated hydrogenated polyfarnesene, hydrogenated castor oil, and dimer acid-based polyester polyol, and / or 2-Ethyl-1,3-hexanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, isosorbide, C 18 diols selected from one or more of dimer diol, 2-butyl-2-ethyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, and 2,2-diethyl-1,3-propanediol, preferably 2-ethyl-1,3-hexanediol, C 18 diols selected from one or more of dimer diol and 2-butyl-2-ethyl-1,3-propanediol; and / or A triol selected from one or more of trimethylolpropane, triethanolamine, diethanolamine, 1,2,6-hexanetriol, phloroglucinol (1,3,5-trihydroxybenzene), and glycerol, more preferably 1,2,6-hexanetriol.
[0030] In contrast, prior art isocyanate-functional acrylated polyurethanes are typically formed from polyether polyols, polyester polyols, polycaprolactone polyols, polycarbonate polyols, and polylactone polyols. Polyether and polyester polyols have proven in the past to give poor results when formulated into conformal coatings due to poor electrical properties, especially Surface Insulation Resistance (SIR), in high temperature / high humidity ("harsh") environments, such as 85% RH and 85°C, conditions commonly used to test conformal coatings for automotive applications. Polyether and polyester polyol-based polyurethane acrylate oligomers tend to degrade under these automotive test conditions, primarily by oxidation and hydrolysis. Furthermore, their low temperature performance is generally unacceptable for use in conformal coatings. Conformal coatings for automotive and aerospace applications must remain flexible at temperatures as low as -60°C. In the automotive industry, -40°C is the accepted standard test temperature for evaluating low temperature performance. Current conformal coatings utilizing polyester polyol-based polyurethane acrylate oligomers do not tend to retain their mechanical properties (elongation (flexibility), tensile strength, modulus) when aged at sub-ambient temperatures, especially at elevated temperatures. Relatively low initial elongation values (samples aged and tested at ambient temperature) of approximately 50% decrease to unacceptable levels upon thermal aging / testing at sub-ambient temperatures. As observed by the inventors of the present application, elongation values below 50% generally lead to premature failure of the conformal coating when subjected to thermal shock testing. As the conformal coating loses flexibility, extensive cracking of the coating becomes evident, often after only a few hundred cycles.
[0031] The glass transition temperature of the final conformal coating is also very important. A glass transition temperature significantly higher than -40°C may also cause stress cracking during thermal shock testing. The isocyanate-functional acrylated polyurethanes of the present application formed with the polyols listed above may exhibit improved properties over commercially available polyurethane acrylate oligomers (recommended and / or used in current radiation curable conformal coatings) due to their unique composition and low glass transition temperature. In particular, compositions containing isocyanate-functional acrylated polyurethanes formed with the polyols listed above may exhibit particularly good flexibility and low temperature performance, along with improved SIR performance. The compositions may still be cured via a primary cure mechanism in the "line of sight" area (UV / UV-LED light polymerizing acrylate groups) and a secondary cure mechanism in the "shadow area" of the circuit board (isocyanate moisture reaction).
[0032] The polyol is preferably 500 to 3000 gmol -1 , more preferably 1000 to 2000 gmol -1 , and even more preferably about 2000 gmol -1 It has a number average molar mass of
[0033] The polyol preferably has a functionality of 1.9 to 2.5 and / or a hydroxyl value of 50 to 250 mg KOH / g.
[0034] The diisocyanate is preferably 1,3-bis(1-isocyanato-1-methylethyl)benzene (TMXDI, tetramethylxylylene diisocyanate), 5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane (IPDI, isophorone diisocyanate), 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate), 1,6-diisocyanatohexane (HDI, hexamethylene diisocyanate), 4,4'-diisocyanatodicyclohexylmethane (H 12The polyols include one or more of 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate), 1,5-diisocyanatopentane (PDI, 1,5-pentamethylene diisocyanate), and preferably 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate). This can result in cured compositions that exhibit particularly good flexibility and low temperature performance, along with improved SIR. Prior art isocyanate-functional acrylated polyurethanes are typically formed from aromatic diisocyanates (e.g., TDI, toluene diisocyanate). This exacerbates the problem of poor retention of tensile properties / poor thermal shock (again with prior art polyol types), as the aromatic character of the resulting polymers means that they are more susceptible to oxidative degradation during aging at high temperature / high humidity.
[0035] The hydroxyalkyl acrylate preferably comprises one or more of 2-hydroxyethyl acrylate, 3-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl methacrylate, and 4-hydroxybutyl methacrylate, more preferably 4-hydroxybutyl acrylate. Such hydroxyalkyl acrylates have longer carbon chains than the hydroxyalkyl acrylates used to form conventional isocyanate-functional acrylated polyurethanes used in conformal coatings. This can result in cured compositions that exhibit particularly good flexibility and low temperature performance, along with improved SIR.
[0036] In a particularly preferred embodiment, the isocyanate-functional acrylated polyurethane is the reaction product of reactants including: Hydroxy-terminated hydrogenated polybutadiene, Hydroxy-terminated hydrogenated polyfarnesene, Hydrogenated castor oil, Dimer acid-based polyester polyol, 2-ethyl-1,3-hexanediol, C 18 one or more of dimer diol and 1,2,6-hexanetriol; 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate); and 4-Hydroxybutyl acrylate.
[0037] To form isocyanate-functional acrylated polyurethanes from the above-mentioned types of reaction products, a catalyst is preferably used to increase the rate and / or selectivity of the reaction or to reduce the temperature that may be required. Suitable catalysts are known in the art, such as metal complexes and tertiary amines. Among metal-based catalysts, organotin compounds (DBTL, DOTL, tin carboxylates, etc.) are very commonly used in the synthesis of polyurethanes. They offer very good performance but have an unfavorable toxicity profile. Other metal catalysts have been developed that show similar performance / reactivity as tin-based materials, while at the same time being much more user- and environmentally friendly. Notable examples are compounds of zirconium, zinc, and bismuth. Preferred catalysts include bismuth carboxylates to catalyze the reaction of isocyanates with hydroxyl-containing reagents. Commercially available examples of such catalysts include K-Kat XC-B221, K-Kat XK651, and K-Kat 6212 from King Industries, and Tibkat 716 and Tibkat 720 from Tib Chemicals.
[0038] The composition preferably comprises 45-60% by weight of acrylic monomer, more preferably 50-60% by weight of acrylic monomer. The presence of such an amount of acrylic monomer may further improve the properties of retention of properties during heat aging, preferably low glass transition temperature, preferably high elasticity, and slower and more controlled polymerization process during UV curing. The acrylic monomer may be considered to be a reactive diluent.
[0039] The acrylic monomer preferably comprises a linear alkyl acrylate comprising from 4 to 12 carbon atoms, more preferably from 6 to 12 carbon atoms, and even more preferably from 8 to 10 carbon atoms. Preferably, the linear alkyl acrylate comprises octadecyl acrylate.
[0040] In addition to the linear alkyl acrylate, the acrylic monomer may further comprise a diacrylate, preferably a diacrylate selected from one or both of 1,6-hexanediol diacrylate and 3-methyl-1,5-pentanediol diacrylate. Such species are particularly effective reactive diluents in combination with other components of the composition.
[0041] The acrylic monomers may also include cyclic acrylates, more preferably tetrahydrofurfuryl acrylate, cyclic trimethylolpropane formal acrylate, t-butylcyclohexanol acrylate, 3,3,5-trimethylcyclohexyl acrylate, isobornyl acrylate, and 2-phenoxyethyl acrylate, even more preferably tetrahydrofurfuryl acrylate. Such species are particularly effective reactive diluents in combination with other components of the composition.
[0042] The photoinitiator preferably comprises: alpha-hydroxyketone photoinitiators, and / or Phenylphosphine oxide photoinitiators, and / or Ethylphenylglyoxylate type photoinitiator.
[0043] More preferably, the photoinitiator comprises: Alpha-hydroxyketone photoinitiators, Phenylphosphine oxide photoinitiators, and Ethylphenylglyoxylate type photoinitiator.
[0044] Such photoinitiator combinations may result in a particularly controlled polymerization process during UV curing. Alpha-hydroxyketone-based photoinitiators may result in a surface cure of the composition. Commercially available examples of suitable alpha-hydroxyketone-based photoinitiators include Darocur™ / Irgacure 1173™ and Double cure™ 173. Phenylphosphine oxide-based photoinitiators may result in a through cure / deep cure of the composition. Commercially available examples of suitable phenylphosphine oxide-based photoinitiators include Irgacure™ 819 and Doublecure™ 1819. Methylphenylglyoxylate-type photoinitiators may be particularly effective in controlling the degree of cure to minimize internal stresses during cure and prevent yellowing and excessive odor after cure. A commercially available example of a methylphenylglyoxylate-type photoinitiator is Doublecure™ 200.
[0045] The alpha-hydroxyketone photoinitiator preferably comprises 2-hydroxy-2-methyl-1-phenyl-propan-1-one. Such photoinitiators can be particularly effective in effecting a surface cure of the composition.
[0046] Phenylphosphine oxide photoinitiators preferably include phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphinate, and / or diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide. Such photoinitiators may be particularly effective in providing a through / deep cure of the composition.
[0047] The ethylphenylglyoxylate type photoinitiator preferably includes methyl benzoylformate. Such photoinitiators can be particularly effective in controlling the rate of cure to minimize internal stresses during cure and to prevent yellowing and excessive odor after cure.
[0048] The photoinitiator preferably comprises a thioxanthone type initiator, which preferably comprises 2-isopropylthioxanthone, and a tertiary amine synergist, which preferably comprises ethyl-4-(dimethylamino)benzoate. The combination of photoinitiator and synergist can be particularly effective in providing a good balance between surface cure and penetration (deep) cure of the composition. Commercially available examples of thioxanthone type photoinitiators and synergists are Ominrad™ ITX, Speedcure™ ITX, and Omnirad™ EDB.
[0049] The composition preferably contains 3.8 to 5.2 wt % photoinitiator, more preferably 4 to 4.5 wt % photoinitiator.
[0050] The antifoaming agent preferably comprises a polyether siloxane, which is a particularly effective antifoaming agent when used in combination with other components of the composition.
[0051] The composition preferably contains 0.2 to 0.8 wt % of the antifoaming agent, more preferably 0.3 to 0.7 wt % of the antifoaming agent.
[0052] The dehydrating agent preferably comprises p-toluenesulfonyl isocyanate, which is a particularly effective dehydrating agent when used in combination with other components of the composition.
[0053] The composition preferably contains 0.7 to 1.3 wt % of the dehydrating agent, more preferably 0.8 to 1.2 wt % of the dehydrating agent.
[0054] The wetting agent preferably comprises poly[dimethylsiloxane-co-methyl(3-hydroxypropyl)siloxane]-graft-poly(ethylene glycol) methyl ether, which is a particularly effective wetting agent when used in combination with other components of the composition.
[0055] The composition preferably comprises 0.5 to 1.3% by weight of the humectant, more preferably 0.8 to 1.2% by weight of the humectant.
[0056] The coupling agent preferably comprises an acrylate-functional silane and / or a (meth)acrylate-functional silane. Such silanes are particularly effective coupling agents when used in combination with other components of the composition.
[0057] The composition preferably contains 1 to 2% by weight of coupling agent, more preferably 1.0 to 1.5% by weight of coupling agent.
[0058] Traditionally, lower viscosity conformal coating compositions have been believed to flow better onto the surface of a PCB than higher viscosity alternatives, however, reducing the viscosity of the conformal coating composition can encourage excessive flow under components, which can make complete post-cure difficult.
[0059] However, the inventors have discovered that tailoring the rheology of the conformal coating composition, rather than simply tailoring the viscosity, is highly beneficial. The conformal coating compositions described herein preferably contain a rheology modifier.
[0060] The rheology modifier preferably comprises a polyamide wax, preferably in the form of crystalline fibers (polyamide wax with crystalline fibers). Advantageously, the use of polyamide wax may allow the composition to be applied to the PCB by selective spray coating. This is because polyamide wax can introduce thixotropy into the system. Thixotropy is a shear thinning property that imparts low viscosity at high shear rates and high viscosity at low shear rates. Selective spray application is a high shear process, meaning that the coating is applied to the PCB at a low viscosity to allow good flow and perfect conformity to the PCB surface. After application, if low shear conditions prevail, the coating viscosity may undergo a time-dependent recovery to the initial high viscosity system. This minimizes excess flow (splash, overspray) under components and at the board edges, i.e., controlled flow. This feature may also make it possible to ensure complete coverage of the edges of the components of the PCB, an issue that has caused problems with many conventional conformal coatings. Sharp edges / component legs of components generally do not coat well enough using low viscosity coating compositions, leading to PCB failure as they become thin and weak areas in the conformal coating. The conformal coating composition of the present invention aims to address this. Without being bound by theory, it is believed that the crystalline fibers of the polyamide wax form an interacting network within the conformal coating composition. This network can be disrupted under high shear conditions, but quickly re-establishes itself and returns to its original state when those shear forces are removed. In this regard, the composition preferably exhibits a thixotropy index of 1.5 to 3.5. This can be achieved by the use of polyamide wax.
[0061] The composition preferably further comprises a UV tracer, which can advantageously result in the composition glowing blue under black light.
[0062] The UV tracer preferably comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole), which is a particularly effective UV tracer in combination with other components of the composition.
[0063] The composition preferably contains 0.1 to 0.5% by weight of the UV tracer, more preferably 0.2 to 0.4% by weight of the UV tracer.
[0064] The composition preferably includes an odor masking agent, which makes the composition more pleasant to use.
[0065] The odor masking agent preferably comprises one or both of dimethyloct-7-en-2-ol and butyl cyclohexyl acetate, preferably both. Such species are particularly effective odor masking agents in combination with other components of the composition.
[0066] In a further aspect, the present invention provides a method of conformally coating a substrate, comprising the steps of: Providing a substrate; Providing a composition as described herein; depositing the composition onto at least a portion of the substrate; exposing the coated substrate to actinic radiation; The present invention provides a method comprising:
[0067] The advantages and preferred features of the first aspect apply equally to this aspect.
[0068] Depositing the composition onto at least a portion of the substrate may include one or more of brushing, spraying, dispensing, and dip coating.
[0069] The actinic radiation is preferably UV, for example UV-LED.
[0070] The substrate preferably comprises a circuit board or an electronic component.
[0071] In a further aspect, the present invention provides a substrate coated with the composition described herein. The advantages and preferred features of the first aspect apply equally to this aspect.
[0072] In a further aspect, the present invention provides a UV and moisture curable conformal coating composition comprising an isocyanate-functional acrylated polyurethane, the isocyanate-functional acrylated polyurethane being the reaction product of reactants comprising the following species: a polyol, preferably an amorphous polyol; a diisocyanate, preferably a branched diisocyanate, and Hydroxyalkyl acrylate.
[0073] The advantages and preferred features of the first aspect apply equally to this aspect.
[0074] In a further aspect, the present invention provides a UV and moisture curable conformal coating composition comprising: 25 to 65 weight percent of an isocyanate-functional acrylated polyurethane; 30 to 65% by weight of an acrylic monomer; and optionally one or more of the following: 3.5 to 5.5 wt. % of a photoinitiator; 0.1 to 1% by weight of a defoamer, 0.5 to 1.5% by weight of a dehydrating agent, 0.2 to 1.5% by weight of a wetting agent, 0.5 to 2.5 weight percent of a coupling agent, and 0.1-2.5 wt.% of a rheology modifier.
[0075] The advantages and preferred features of the first aspect apply equally to this aspect.
[0076] The invention will now be further described with reference to the following numbered clauses:
[0077] 1. A UV and moisture curable conformal coating composition comprising: 52 to 75 weight percent of an isocyanate-functional acrylated polyurethane; 20 to 43% by weight of an acrylic monomer; 3.5 to 5.5 wt. % of a photoinitiator; 0.5 to 1% by weight of a defoamer, 0.2 to 0.5% by weight of a dehydrating agent, 0.3 to 0.5 weight percent of a wetting agent, and 0.1-0.3 wt.% of a coupling agent.
[0078] 2. The composition according to paragraph 1, comprising from 55 to 70% by weight of an isocyanate-functional acrylated polyurethane, preferably from 57 to 65% by weight of an isocyanate-functional acrylated polyurethane.
[0079] 3. The composition of claim 1 or 2, wherein the isocyanate-functional acrylated polyurethane is thermoplastic.
[0080] 4. The composition of any one of the preceding claims, wherein the isocyanate-functional acrylated polyurethane is an elastomer.
[0081] 5. The composition according to any one of the preceding paragraphs, comprising 25 to 41% by weight of an acrylic monomer, preferably 30 to 40% by weight of an acrylic monomer.
[0082] 6. The photoinitiator is alpha-hydroxyketone photoinitiators, and / or Phenylphosphine oxide photoinitiators, and / or Ethylphenylglyoxylate-type photoinitiator The composition of any one of the preceding claims, comprising:
[0083] 7. The photoinitiator is Alpha-hydroxyketone photoinitiators, Phenylphosphine oxide photoinitiators, and Ethylphenylglyoxylate-type photoinitiator The composition of any one of the preceding claims, comprising:
[0084] 8. The composition of claim 6 or 7, wherein the alpha-hydroxyketone photoinitiator comprises 2-hydroxy-2-methyl-1-phenyl-propan-1-one.
[0085] 9. The composition of any one of paragraphs 6 to 8, wherein the phenylphosphine oxide photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)-phosphine oxide.
[0086] 10. The composition of any one of items 6 to 9, wherein the ethylphenylglyoxylate type photoinitiator comprises methyl benzoylformate.
[0087] 11. The composition of any one of the preceding claims, wherein the antifoam agent comprises a polyether siloxane.
[0088] 12. The composition of any one of the preceding claims, wherein the dehydrating agent comprises p-toluenesulfonyl isocyanate.
[0089] 13. The composition of any one of the preceding clauses, wherein the wetting agent comprises poly[dimethylsiloxane-co-methyl(3-hydroxypropyl)siloxane]-graft-poly(ethylene glycol) methyl ether.
[0090] 14. The composition of any one of the preceding claims, wherein the coupling agent comprises an acrylate-functional silane.
[0091] 15. The composition of any one of the preceding claims, further comprising a reactive diluent.
[0092] 16. The composition of paragraph 15, wherein the reactive diluent comprises one or both of 3,3,5-trimethylcyclohexyl acrylate and tricyclodecane dimethanol diacrylate, preferably both.
[0093] 17. The composition of any one of the preceding claims, further comprising a UV tracer.
[0094] 18. The composition of paragraph 17, wherein the UV tracer comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole.
[0095] 19. The composition of any one of the preceding claims, further comprising an odor masking agent.
[0096] 20. The composition of paragraph 19, wherein the odor masking agent comprises one or both of dimethyloct-7-en-2-ol and butyl cyclohexyl acetate, preferably both.
[0097] 21. A method for conformally coating a substrate, comprising the steps of: Providing a substrate; Providing a composition according to any one of the preceding paragraphs; depositing the composition onto at least a portion of the substrate; exposing the coated substrate to actinic radiation; A method comprising:
[0098] 22. The method of claim 21, wherein the substrate comprises a circuit board or an electronic component.
[0099] 23. A substrate coated with the composition described in any one of items 1 to 20.
[0100] The advantages and preferred features of the previous aspects apply equally to the subject matter of these articles. [Brief description of the drawings]
[0101] [Figure 1] 4 shows the results of SIR testing of sample 1 and two commercially available oligomers. [Diagram 2] The elongation value is shown. [Diagram 3] The values of the elastic modulus are given. EXAMPLES
[0102] The invention is further described by reference to the following examples.
[0103] General synthesis of isocyanate-functional acrylated polyurethane oligomers: In the first stage, a diisocyanate is reacted with a polyol (and / or diol / triol) at elevated temperature under nitrogen with a catalyst to obtain an isocyanate-terminated "prepolymer." This prepolymer is further reacted in the second stage with a hydroxyalkyl acrylate under air to form an isocyanate-functional polyurethane acrylate oligomer. The elevated temperature and catalyst are used to shorten the total reaction time, to reduce the temperature required for the reaction, and / or to improve the selectivity of the reaction between the isocyanate groups in the diisocyanate and the hydroxyl groups of the other reactants.
[0104] An exemplary reaction scheme is as follows:
[0105] [ka]
[0106] The reaction scheme above shows steps 1 and 2 as well as an idealized structure of the product, an isocyanate-functional polyurethane acrylate oligomer.
[0107] In the reaction scheme (Step 2, acrylation), the R3 group of the hydroxyalkyl acrylate can be as follows: -CH2CH2- 2-Hydroxyethyl acrylate -CH2CH2CH2- 3-Hydroxypropyl acrylate -CH2CH2CH2CH2- 4-Hydroxybutyl acrylate
[0108] In the reaction scheme (Step 1), representative structures of the reagents used are as follows: Polyols / Diols: C36 dimer acid based polyester polyols:
[0109] [ka] Hydrogenated polybutadiene:
[0110] [ka] C36 Dimer Diol:
[0111] [ka] Isocyanates: TMDI
[0112] [ka]
[0113] Oligomer synthesis, sample 1: 2,2,4(2,4,4)-trimethylhexamethylene diisocyanate (0.21 moles, 44.10 g) and bismuth carboxylate catalyst (0.1 wt. % based on total batch) were added to a round-bottom reaction flask equipped with a thermometer, stirrer, and nitrogen line. Nitrogen was introduced into the flask as an initial purge, followed by a constant flow of approximately 1 mL / min to maintain an inert atmosphere. Molar mass 2000 gmol -1 C 36Dimer acid-based polyester polyol (0.1 mole, 200 g) was added to the flask. The reaction was carried out at 80° C. for 2 hours, thereby forming an isocyanate-terminated prepolymer. The end point of the reaction was when the theoretical isocyanate % was achieved (measured by back titration with di-n-butylamine according to ISO 14896) and the FTIR spectrum showed bands characteristic of an isocyanate-terminated polyurethane prepolymer, bounded by the absence of bands associated with hydroxyl groups. After this stage was completed, the nitrogen line was replaced with a dry air line. Again, following the initial purge, a constant flow rate of approximately 1 mL / min was applied to maintain an oxygen-rich atmosphere. The temperature was reduced from 80° C. to 50° C., and then 100 ppm of a polymerization inhibitor, such as phenothiazine, MEHQ, etc., was added to the flask (to prevent self-polymerization of the acrylate groups). Once this was completely dissolved / dispersed in the isocyanate terminated polyurethane prepolymer, 4-hydroxybutyl acrylate (0.11 moles, 15.86 g) was added to the flask. The reaction was allowed to proceed at 50-60°C for 1 hour. Again, the end point of the reaction was when the theoretical isocyanate % was achieved and the FTIR spectrum showed bands characteristic of isocyanate terminated polyurethane prepolymer, bounded by the presence of bands associated with acrylate groups. A viscous (625000 mPa.s at 20°C), colorless isocyanate functional urethane acrylate oligomer was obtained in high yield (>95%). The final isocyanate content was 1.78% with an acrylate:isocyanate ratio of 1:1.
[0114] Oligomer synthesis, sample 2: This polyurethane acrylate oligomer was prepared using the same process as described in Example 1. 2,2,4(2,4,4)-trimethylhexamethylene diisocyanate (1.356 moles, 284.76 g) and bismuth carboxylate catalyst (0.1 wt % based on total batch) were added to a mass of approximately 540 gmol -1 C 36Reacted with dimer acid based polyol (0.645 moles, 349.59 g) to form an isocyanate terminated prepolymer. 4-Hydroxybutyl acrylate (0.71 moles, 102.41 g) was then added to the flask and reacted to form a polyurethane acrylate oligomer. A viscous (103,000 mPa.s at 20°C), straw colored isocyanate functional urethane acrylate oligomer was obtained in high yield (>95%). The final isocyanate content was 4.31% with an acrylate:isocyanate ratio of 1:1.
[0115] Oligomer synthesis, sample 3: This polyurethane acrylate oligomer was prepared using the same process as described in Example 1. 2,2,4(2,4,4)-trimethylhexamethylene diisocyanate (0.21 moles, 44.10 g) and bismuth carboxylate catalyst (0.01 wt. % based on total batch) were added to a 2000 g / mol -1 of hydrogenated polybutadiene polyol (0.1 moles, 200 g) to form an isocyanate-terminated prepolymer. 2-Hydroxyethyl acrylate (0.11 moles, 12.77 g) was then added to the flask and allowed to react to form a polyurethane acrylate oligomer. A viscous (750,000 mPa.s at 20°C), straw-colored isocyanate-functional urethane acrylate oligomer was obtained in high yield (>95%). The final isocyanate content was 1.73% with an acrylate:isocyanate ratio of 1:1.
[0116] Testing of Isocyanate Functional Acrylated Polyurethane Oligomers: Improved surface insulation resistance (SIR) This is an important property of the conformal coating and is routinely evaluated under extreme conditions to check for (a) the initial SIR value, (b) any trend in the SIR value over time, and (c) any evidence of corrosion on the PCB, etc. A downward trend indicates degradation of the conformal coating, leading to premature failure of the PCB via corrosion, dendrite formation, tin whiskers, etc.
[0117] Laboratory testing of oligomer samples 1-3 suggests that higher SIR values (one order of magnitude) can be achieved than the commercially available oligomers. SIR test results for sample 1 and two commercially available oligomers are shown in Figure 1. Commercial Example 1 is an isocyanate aliphatic functional urethane acrylate. Commercial Example 2 is an oligomer with UV, isocyanate, and siloxane functionality. As can be seen, sample 1 achieves an average SIR value of 9.31 with a stable linear response over the test period, indicating that the coating is performing well and does not show any signs of degradation. Both commercially available oligomers return lower average SIR values of 8.42 and 7.98 for Commercial Examples 1 and 2, respectively. Furthermore, the response of these oligomers is not stable and shows a clear downward trend. The stable response of sample 1 at 85% relative humidity and 85°C is excellent. The minimum SIR value acceptable for automotive applications is a Log of 8. 10 and somewhat above Sample 1. Conversely, all of the commercially available oligomers perform poorly in this test and fail to meet this criterion during extended testing based on the trend for decreasing values over time.
[0118] Improved retention of tensile properties The tensile properties of the oligomers and commercial examples of Samples 1-3 were measured initially (after primary and secondary curing) and after aging at 130°C. Testing was performed at ambient and -40°C. Sample 1 showed higher elongation and lower modulus values initially and retained a higher degree of these initial properties after aging. The elongation and modulus values are shown in Figures 2 and 3. In terms of elongation, Samples 1, 2, and 3 show a higher level of elasticity / flexibility than both commercial materials when initially tested. They retain elasticity after heat aging and when tested at sub-ambient temperatures. When these two conditions are combined, Samples 1-3 perform exceptionally well.
[0119] The oligomer of Commercial Example 2 has a lower initial elongation value, but tends to be better at retaining this elongation upon heat aging. However, the combination of heat aging and subambient testing returns poor results with elongation decreasing by about 50%. The oligomer of Commercial Example 1 appears to be much poorer than Samples 1-3 in terms of elasticity retention. The initial elongation value of about 50% decreases by a factor of 10 (to about 5%) after heat aging and subambient testing. The test sample breaks almost immediately upon initiation of testing. Commercial Examples 1 and 2 appear to exhibit primarily plastic deformation when tested at subambient temperatures, with no appreciable recovery (return to original sample dimensions) upon returning to room temperature. Samples 1-3 appear to exhibit primarily elastic deformation, with rapid recovery (samples return to original dimensions in less than 1 minute at room temperature).
[0120] With regard to modulus, which is a measure of the "stiffness" of a sample, the higher the modulus, the stiffer and less elastic the material. All oligomers tested started out with a very low modulus, indicative of a soft elastic material. Upon aging, samples 1-3 showed a moderate increase of an order of magnitude in modulus values, from 0.5-1.0 MPa to 15-45 MPa, but as noted above, this did not appear to significantly affect elasticity / recovery. However, both commercial materials showed a significant increase in modulus when tested at sub-ambient temperatures, which was exacerbated when aged at elevated temperatures prior to testing. When unaged samples (stored at 25°C prior to testing) were tested at -40°C, a two order of magnitude increase was returned, as well as a two order of magnitude increase for samples aged at the same test temperatures.
[0121] This manifests as increased stiffness and poor recovery for these samples. Without wishing to be bound by theory, these changes in tensile properties are likely due to increased crystallinity (and associated intermolecular bonding) in the commercial material compared to Samples 1-3 oligomers. This also contributes to poor thermal shock performance. The above test regime is designed to simulate what a conformal coating (in this case, an oligomer) would be exposed to under real-world service conditions.
[0122] Improved thermal shock resistance Thermal shock testing showed that samples 1-3 exhibited improved thermal shock resistance compared to the commercial oligomer.
[0123] Lowering of Tg (glass transition temperature) Tg tests showed that samples 1-3 exhibited lower Tg temperatures compared to the commercial oligomers.
[0124] The foregoing detailed description has been provided by way of illustration and description and is not intended to limit the scope of the appended claims. Many variations of the presently preferred embodiments described herein will be apparent to those of ordinary skill in the art and remain within the scope of the appended claims and their equivalents.
Claims
1. 1. A UV and moisture curable conformal coating composition comprising: 25 to 65 weight percent of an isocyanate-functional acrylated polyurethane; 30 to 65% by weight of an acrylic monomer; 3.5 to 5.5 wt. % of a photoinitiator; 0.1 to 1 wt. % of an antifoaming agent, 0.5 to 1.5 wt. % of a dehydrating agent; 0.2 to 1.5 wt. % of a wetting agent, and 0.5 to 2.5 wt. % of a coupling agent; 1. A UV and moisture curable conformal coating composition comprising:
2. 2. The composition of claim 1, comprising 30 to 50% by weight of the isocyanate-functional acrylated polyurethane, preferably 35 to 45% by weight of the isocyanate-functional acrylated polyurethane.
3. The composition of claim 1 or 2, wherein the isocyanate-functional acrylated polyurethane is thermoplastic.
4. The composition of any one of claims 1 to 3, wherein the isocyanate-functional acrylated polyurethane is an elastomer.
5. The composition of any one of claims 1 to 4, wherein the isocyanate-functional acrylated polyurethane has a ratio of acrylate functional groups to isocyanate functional groups of from 2:1 to 1:
2.
6. The isocyanate-functional acrylated polyurethane may be selected from the group consisting of the following species: a polyol, preferably an amorphous hydrophobic polyol; a diisocyanate, preferably a branched diisocyanate, and Hydroxyalkyl acrylate, The composition of any one of claims 1 to 5, which is a reaction product of reactants comprising:
7. The polyol is one or more of hydroxy-terminated polybutadiene, hydroxy-terminated hydrogenated polybutadiene, hydroxy-terminated polyisoprene, hydroxy-terminated polyolefin, hydroxy-terminated polyfarnesene, hydroxy-terminated hydrogenated polyfarnesene, castor oil, hydrogenated castor oil, and dimer acid-based polyester polyol (preferably C36), preferably one or more of hydroxy-terminated hydrogenated polybutadiene, hydroxy-terminated hydrogenated polyfarnesene, hydrogenated castor oil, and dimer acid-based polyester polyol, and / or 2-Ethyl-1,3-hexanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, isosorbide, C 18 Diols selected from one or more of dimer diol, 2-butyl-2-ethyl-1,3-propanediol, 2,2-dimethyl-1,3-propanediol, and 2,2-diethyl-1,3-propanediol, preferably 2-ethyl-1,3-hexanediol, C 18 diols selected from one or more of dimer diol, and 2-butyl-2-ethyl-1,3-propanediol, and / or 7. The composition of claim 6, comprising a triol selected from one or more of trimethylolpropane, triethanolamine, diethanolamine, 1,2,6-hexanetriol, phloroglucinol (1,3,5-trihydroxybenzene), and glycerol, preferably 1,2,6-hexanetriol.
8. The polyol is 500 to 3000 gmol -1 , preferably 1000 to 2000 gmol -1 , more preferably about 2000 gmol -1 8. The composition according to claim 6 or 7, having a molar mass of
9. The composition according to any one of claims 6 to 8, wherein the polyol has a functionality of from 1.9 to 2.5 and / or a hydroxyl number of from 50 to 250 mg KOH / g.
10. The diisocyanate is 1,3-bis(1-isocyanato-1-methylethyl)benzene (TMXDI, tetramethylxylylene diisocyanate), 5-isocyanato-1-(isocyanatomethyl)-1,3,3-trimethylcyclohexane (IPDI, isophorone diisocyanate), 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate), 1,6-diisocyanatohexane (HDI, hexamethylene diisocyanate), 4,4'-diisocyanatodicyclohexylmethane (H 12 10. The composition according to any one of claims 6 to 9, comprising one or more of 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate), 1,5-diisocyanatopentane (PDI, 1,5-pentamethylene diisocyanate), and preferably 1,6-diisocyanato-2,2,4(2,4,4)-trimethylhexane (TMDI, trimethylhexamethylene diisocyanate).
11. 11. A composition according to any one of claims 6 to 10, wherein the hydroxyalkyl acrylate comprises one or more of 2-hydroxyethyl acrylate, 3-hydroxypropyl acrylate, 4-hydroxybutyl acrylate, 2-hydroxyethyl methacrylate, 3-hydroxypropyl methacrylate and 4-hydroxybutyl methacrylate, preferably 4-hydroxybutyl acrylate.
12. A composition according to any one of the preceding claims, comprising from 45 to 60% by weight of acrylic monomer, preferably from 50 to 60% by weight of acrylic monomer.
13. The acrylic monomer is 13. The composition according to any one of claims 1 to 12, comprising a linear alkyl acrylate comprising from 4 to 12 carbon atoms, preferably from 6 to 12 carbon atoms, more preferably from 8 to 10 carbon atoms.
14. The acrylic monomer is The composition of any one of claims 1 to 13, comprising one or both of 1,6-hexanediol diacrylate and 3-methyl-1,5-pentanediol diacrylate.
15. The acrylic monomer is 15. The composition according to any one of claims 1 to 14, comprising a cyclic acrylate, preferably tetrahydrofurfuryl acrylate, cyclic trimethylolpropane formal acrylate, t-butyl cyclohexanol acrylate, 3,3,5-trimethylcyclohexyl acrylate, isobornyl acrylate, and 2-phenoxyethyl acrylate, more preferably tetrahydrofurfuryl acrylate.
16. The photoinitiator is alpha-hydroxyketone photoinitiators, and / or Phenylphosphine oxide photoinitiators, and / or Ethylphenylglyoxylate-type photoinitiator The composition according to any one of claims 1 to 15, comprising:
17. The photoinitiator is alpha-hydroxyketone photoinitiators, Phenylphosphine oxide photoinitiators, and Ethylphenylglyoxylate-type photoinitiator The composition according to any one of claims 1 to 16, comprising:
18. 18. The composition of claim 16 or 17, wherein the alpha-hydroxyketone photoinitiator comprises 2-hydroxy-2-methyl-1-phenyl-propan-1-one.
19. 19. The composition of any one of claims 16 to 18, wherein the phenylphosphine oxide photoinitiator comprises phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, ethyl(2,4,6-trimethylbenzoyl)phenylphosphinenate, and / or diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide.
20. The composition of any one of claims 16 to 19, wherein the ethylphenylglyoxylate type photoinitiator comprises methyl benzoylformate.
21. The photoinitiator is a thioxanthone type initiator, preferably comprising 2-isopropylthioxanthone; and Tertiary amine synergists, preferably including ethyl-4-(dimethylamino)benzoate The composition according to any one of claims 16 to 20, comprising:
22. A composition according to any one of the preceding claims, comprising 3.8 to 5.2 wt% photoinitiator, preferably 4 to 4.5 wt% photoinitiator.
23. The composition of any one of claims 1 to 22, wherein the antifoam agent comprises a polyether siloxane.
24. A composition according to any one of the preceding claims, comprising 0.2 to 0.8 wt.% of an antifoaming agent, preferably 0.3 to 0.7 wt.% of an antifoaming agent.
25. The composition of any one of claims 1 to 24, wherein the dehydrating agent comprises p-toluenesulfonyl isocyanate.
26. A composition according to any one of the preceding claims, comprising 0.7 to 1.3 wt.% of a dehydrating agent, preferably 0.8 to 1.2 wt.% of a dehydrating agent.
27. The composition of any one of claims 1 to 26, wherein the wetting agent comprises poly[dimethylsiloxane-co-methyl(3-hydroxypropyl)siloxane]-graft-poly(ethylene glycol) methyl ether.
28. A composition according to any preceding claim, comprising 0.5 to 1.3% by weight of humectant, preferably 0.8 to 1.2% by weight of humectant.
29. The composition of any one of claims 1 to 28, wherein the coupling agent comprises an acrylate or methacrylate functional silane.
30. A composition according to any one of the preceding claims, comprising 1 to 2% by weight of a coupling agent, preferably 1.3 to 1.8% by weight of a coupling agent.
31. The composition of any one of claims 1 to 30, further comprising a rheology modifier.
32. 32. The composition of claim 31 , wherein the rheology modifier comprises a polyamide wax.
33. 33. The composition according to claim 31 or 32, comprising 0.1 to 2.5 wt.% of a rheology modifier, preferably 0.2 to 0.8 wt.% of a rheology modifier, more preferably 0.3 to 0.7 wt.% of a rheology modifier.
34. The composition of any one of claims 1 to 33, further comprising a UV tracer.
35. 35. The composition of claim 34, wherein the UV tracer comprises 2,5-thiophenediylbis(5-tert-butyl-1,3-benzoxazole.
36. A composition according to claim 34 or 35, comprising 0.1 to 0.5% by weight of UV tracer, preferably 0.2 to 0.4% by weight of UV tracer.
37. The composition of any one of claims 1 to 36, further comprising an odor masking agent.
38. 38. The composition of claim 37, wherein the odor masking agent comprises one or both of dimethyloct-7-en-2-ol and butyl cyclohexyl acetate, preferably both.
39. 1. A method of conformally coating a substrate, comprising: Providing a substrate; Providing a composition according to any one of claims 1 to 38; depositing the composition onto at least a portion of the substrate; exposing the coated substrate to actinic radiation; A method comprising:
40. 40. The method of claim 39, wherein the substrate comprises a circuit board or an electronic component.
41. A substrate coated with the composition according to any one of claims 1 to 38.
Citation Information
Patent Citations
Moisture-curable type urethane coating material composition and coating material obtained by recoating the composition
JP2001081400A
Curable composition
JP2015096608A
Active energy ray-curable coating agent composition
JP2015120781A
UV cured varnish and process for preparing the same
US20150225597A1
High-recoverability resin particles and use thereof
WO2016039357A1